2020
DOI: 10.2478/bsrj-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Governing IT in HEIs: Systematic Mapping Review

Abstract: BackgroundHigher Education Institutions (HEIs) are aware of the immense importance of achieving their strategic objectives to increase their impact on the society and to be competitive. As a board responsibility, information technology governance (ITG) plays an important role in the overall HEIs performance. Numerous HEIs are making great efforts to properly govern information technology (IT) by using ITG frameworks.ObjectivesThis study investigates the overall adoption of ITG frameworks in different HEIs thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In this sense, IT governance plays an important role in the overall performance of HEIs [34]. Julianti et al [35] also refer to the importance of IT governance in supporting IT-based educational services and achieving better performance of academic IS, with a view to aligning strategic objectives with the implementation of IT in the HEI environment.…”
Section: Performance and Controlmentioning
confidence: 99%
“…In this sense, IT governance plays an important role in the overall performance of HEIs [34]. Julianti et al [35] also refer to the importance of IT governance in supporting IT-based educational services and achieving better performance of academic IS, with a view to aligning strategic objectives with the implementation of IT in the HEI environment.…”
Section: Performance and Controlmentioning
confidence: 99%
“…As demonstrated by Lunardi et al [20], this efficiency is crucial for an organization to achieve its performance objectives. Previous studies have shown that effective ITG relies heavily on the ITG practices of these mechanisms, ranging from decision-making at the board level to the implementation of IT control [2], [21].…”
Section: Governance Mechanismsmentioning
confidence: 99%
“…Therefore, universities must regularly improve their information technology governance (ITG) to cope with innovation and change and adapt to new technologies. Several authors recommend the effective use of ITG mechanisms in higher education institutions (HEIs) [2]- [6], such as structure, processes, and relational mechanisms [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite ITG's relevance for organizations, empirical studies in this field are still scarce, particularly in universities [18,42]. Universities from many countries have increasingly recognized the importance of ITG [18,42,43]. Complex organizations, such as universities, should frequently review their ITG practices to deal with innovation and changes in their environment and adapt to new technologies [11,17,44].…”
Section: It Governance In Universitiesmentioning
confidence: 99%